Racializing media policy - Smith, Jason A.; Craig, Richard T. (Emerald points., 2023)
Scholars in the Sociology of Race have extensively researched public policy sectors such as housing, taxation, and immigration. However, media policy research has often failed to effectively engage with the critical concept of racialization, driven instead by political and economic perspectives. Racializing Media Policy fills this gap in the sociological, communications, and media studies literatures with its focus on the racialized processes that construct media policy work in the United States. With research that merges subfields of racialization and media policy, explores the US broadcasting policy, and examines racialization without integration and mediating structural challenges, the authors delve into multiple scenarios of racialization in policy. The chapters offer theoretical frameworks and case studies to consider the ways that media policy spaces are embedded with ideologies and praxes surrounding race. Racializing Media Policy contributes to a wider understanding of the role of policy work in the media systems, particularly by examining the ways that race is embedded within those structures. This unique perspective makes the volume an important read for scholars across the Sociology and Media Studies fields, in addition to providing critical context for policymakers.